Financial Health Soundness Measurement of Private Commercial Banks in Bangladesh: An Observation of Selected Banks - Uddin, Mohammad Main; Masud, Abdul Kaium (Journal of Nepalese Business Studies, 2016)
The financial sector is one of the most significant sectors for any country, especially if a country is a developing in nature. In such an environment, banking sector plays the vital role to strengthen the economic conditions. Economic growth and international business is increasing in Bangladesh and private commercial banks especially private sectors play the major roles. Thus it becomes important to measure the financial soundness of the private banks in order to judge their respective position. The study was conducted to measure the financial soundness of selected private commercial banks of Bangladesh for the period 2006-2010. In this paper, an attempt was made to analyze the financial soundness of selected banks using different statistical tools and financial indicators. The study reveals that different financial indicators showed upward trends during the period 2006 to 2010. The study also made a rank of the selected commercial banks based on financial indicators. It was found that a bank with higher deposits, loans & advances, investments, branches, employees does not always mean that has better profitability performance. The study also recommends measures that could be adopted by banks to ensure soundness in their operation. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp. 20-36